Russian-Polish Relations at the Turn of the “Long XII Century”: from the “Pereyaslavl Crisis” to the Death of Roman Galitsky - A. V. Korenevskiy; N. D. Nikolaeva (Научный диалог, 2020)
This article is a continuation of the work “The Polish Vector in the Politics of Vladimir Monomakh and His  Successors: from the Lyubech Congress to the “Pereyaslavl Crisis”, published in the previous issue. The question of the system of Russian-Polish relations during the period of the onset of political fragmentation of Russia (since 1132) and a radical change in the balance of power relative to the Kiev principality is considered in the article. It is proved that the thesis of the religious factor as decisive in Russian-Polish relations does not correspond to the realities of the 30—90s of the 12th century. It is shown that the internal and external political circumstances of the 30—40s of the XII century forced Kiev and Krakow to come closer. It is emphasized that the trend towards rapprochement continues throughout the second half of the 12th century. Particular attention is paid to the nature  of Russian-Polish relations at the turn of the XII-XIII centuries. The authors note that the situation in Russian-Polish relations begins to change dramatically in the first decade of the 13th century. Evidence is given that the reasons for the cardinal changes were associated with the political course of the Galician-Volyn prince Roman Mstislavich and the results of the IV Crusade, which marked the beginning of the civilizational split in Europe.